Technique for Outdoor Test on Concentrating Photovoltaic Cells - Paola Sansoni; Daniela Fontani; Franco Francini; David Jafrancesco; Giacomo Pierucci; Maurizio De Lucia (International Journal of Photoenergy)
Outdoor experimentation of solar cells is essential to maximize their performance and to assess utilization requirements and limits. More generally tests with direct exposure to the sun are useful to understand the behavior of components and new materials for solar applications in real working conditions. Insolation and ambient factors are uncontrollable but can be monitored to know the environmental situation of the solar exposure experiment. A parallel characterization of the photocells can be performed in laboratory under controllable and reproducible conditions. A methodology to execute solar exposure tests is proposed and practically applied on photovoltaic cells for a solar cogeneration system. The cells are measured with concentrated solar light obtained utilizing a large Fresnel lens mounted on a sun tracker. Outdoor measurements monitor the effects of the exposure of two multijunction photovoltaic cells to focused sunlight. The main result is the continuous acquisition of the V-I (voltage-current) curve for the cells in different conditions of solar concentration and temperature of exercise to assess their behavior. The research investigates electrical power extracted, efficiency, temperatures reached, and possible damages of the photovoltaic cell.